2015
DOI: 10.1016/j.micres.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity in the deep-sea sediments of Iheya North and Iheya Ridge, Okinawa Trough

Abstract: In this study, we analyzed the bacterial and archaeal diversities of the deep-sea sediments in Iheya North and Iheya Ridge, Okinawa Trough, using the high-throughput sequencing technology of Illumina MiSeq 2500 platform. Four samples (IN1, IN2, IR1 and IR2) were used in this study, of which IN1 and IN2 were located at regions close to and distant, respectively, from the active hydrothermal vents in Iheya North, while IR1 and IR2 were located at regions close to and distant, respectively, from the active hydrot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
41
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 58 publications
8
41
1
3
Order By: Relevance
“…Thaumarchaeota was relatively more abundant in the microbial communities of Pacmanus than in the microbial communities of Desmos, suggesting a possibly more important role of these archea in ammonia oxidization in the sediment of Pacmanus hydrothermal field. These results are consistent with the previous reports that Proteobacteria is the dominant community in marine environments and was found in deep-sea sediments and hydrothermal systems [18,37]. Likewise, Thaumarchaeota has been observed in the sediments of Southwest Indian Ridge and Okinwa Trough [18,38,39].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Thaumarchaeota was relatively more abundant in the microbial communities of Pacmanus than in the microbial communities of Desmos, suggesting a possibly more important role of these archea in ammonia oxidization in the sediment of Pacmanus hydrothermal field. These results are consistent with the previous reports that Proteobacteria is the dominant community in marine environments and was found in deep-sea sediments and hydrothermal systems [18,37]. Likewise, Thaumarchaeota has been observed in the sediments of Southwest Indian Ridge and Okinwa Trough [18,38,39].…”
Section: Discussionsupporting
confidence: 92%
“…Gammaproteobacteria has been widely detected in deep-sea environments [18,37,4043], and Epsilonproteobacteria was reported to occur in the hydrothermal systems of Mid-Atlantic Ridge, Mariana Arc seamounts, and Okinawa Trough [4446]. In our study, the presence of the genera Sulfurovum , Sulfurimonas , Arcobacter , and Sulfurospirillum within Epsilonproteobacteria suggested that these members potentially participated in sulfur oxidization and reduction as well as nitrate reduction.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations